Somatic and de novo Germline Variants of MEDs in Human Neural Tube Defects - Tian, Tian; Cao, Xuanye; Chen, Yongyan; Jin, Lei; Li, Zhiwen; Han, Xiao; Lin, Ying; Wlodarczyk, Bogdan J.; Finnell, Richard H.; Yuan, Zhengwei; Wang, Linlin; Ren, Aiguo; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Neural tube defects (NTDs) are among the most common and severe congenital defects in humans. Their genetic etiology is complex and remains poorly understood. The Mediator complex (MED) plays a vital role in neural tube development in animal models. However, no studies have yet examined the role of its human homolog in the etiology of NTDs. Methods: In this study, 48 pairs of neural lesion site and umbilical cord tissues from NTD and 21 case-parent trios were involved in screening for NTD-related somatic and germline de novo variants. A series of functional cell assays were performed. We generated a Med12 p.Arg1784Cys knock-in mouse using CRISPR/Cas9 technology to validate the human findings. Results: One somatic variant, MED12 p.Arg1782Cys, was identified in the lesion site tissue from an NTD fetus. This variant was absent in any other normal tissue from different germ layers of the same case. In 21 case-parent trios, one de novo stop-gain variant, MED13L p.Arg1760*, was identified. Cellular functional studies showed that MED12 p.Arg1782Cys decreased MED12 protein level and affected the regulation of MED12 on the canonical-WNT signaling pathway. The Med12 p.Arg1784Cys knock-in mouse exhibited exencephaly and spina bifida. Conclusion: These findings provide strong evidence that functional variants of MED genes are associated with the etiology of some NTDs. We demonstrated a potentially important role for somatic variants in the occurrence of NTDs. Our study is the first study in which an NTD-related variant identified in humans was validated in mice using CRISPR/Cas9 technology.